In Silico Evaluation of the Effectivity of Approved Protease Inhibitors against the Main Protease of the Novel SARS-CoV-2 Virus - Phaedra Eleftheriou (Molecules, 2020)
The coronavirus disease, COVID-19, caused by the novel coronavirus SARS-CoV-2, which first emerged in Wuhan, China and was made known to the World in December 2019 turned into a pandemic causing more than 126,124 deaths worldwide up to April 16th, 2020. It has 79.5% sequence identity with SARS-CoV-1 and the same strategy for host cell invasion through the ACE-2 surface protein. Since the development of novel drugs is a long-lasting process, researchers look for effective substances among drugs already approved or developed for other purposes. The 3D structure of the SARS-CoV-2 main protease was compared with the 3D structures of seven proteases, which are drug targets, and docking analysis to the SARS-CoV-2 protease structure of thirty four approved and on-trial protease inhibitors was performed. Increased 3D structural similarity between the SARS-CoV-2 main protease, the HCV protease and α-thrombin was found. According to docking analysis the most promising results were found for HCV protease, DPP-4, α-thrombin and coagulation Factor Xa known inhibitors, with several of them exhibiting estimated free binding energy lower than −8.00 kcal/mol and better prediction results than reference compounds. Since some of the compounds are well-tolerated drugs, the promising in silico results may warrant further evaluation for viral anticipation. DPP-4 inhibitors with anti-viral action may be more useful for infected patients with diabetes, while anti-coagulant treatment is proposed in severe SARS-CoV-2 induced pneumonia.